European consensus statement on phenotypes of pustular psoriasis. (29th August 2017) - Navarini, A.A.; Burden, A.D.; Capon, F.; Mrowietz, U.; Puig, L.; Köks, S.; Kingo, K.; Smith, C.; Barker, J.N.; ,
Abstract: Pustular psoriasis (PP) is a group of inflammatory skin conditions characterized by infiltration of neutrophil granulocytes in the epidermis to such an extent that clinically visible sterile pustules develop. Because of clinical co‐incidence, PP is currently grouped with psoriasis vulgaris (PV). However, PP and PV are phenotypically different, respond differently to treatments and seem to be distinct on the genetic level. In contrast to PV, the phenotypes of PP are not well defined. Descriptions of each form of PP are discordant among standard dermatology textbooks [ Saurat Dermatologie 2016, Rook's Dermatology 2016, Fitzpatrick's 2012 and Braun‐Falco 2012], encumbering the collection of phenotypically well‐matched groups of patients as well as clinical trials. The European Rare and Severe Psoriasis Expert Network (ERASPEN) was founded to define consensus criteria for diagnosis, deeply phenotype large groups of PP patients, analyse the genetics and pathophysiology and prepare for prospective clinical trials. This work reviews historical aspects of these conditions, new genetic findings and presents our initial considerations on the phenotypes of PP and a consensus classification of clinical phenotypes that will be used as a baseline for further, prospective studies of PP. Generalized pustular psoriasis (GPP) is defined as primary, sterile, macroscopically visible pustules on non‐acral skin (excluding cases where pustulation is restricted to psoriatic plaques). GPP can occur with or without systemic inflammation, with or without PV and can either be a relapsing (>1 episode) or persistent (>3 months) condition. Acrodermatitis continua of Hallopeau (ACH) is characterized by primary, persistent (>3 months), sterile, macroscopically visible pustules affecting the nail apparatus. Palmoplantar pustulosis (PPP) has primary, persistent (>3 months), sterile, macroscopically visible pustules on palms and/or soles and can occur with or without PV.